Performance of a hybrid direct ethylene glycol fuel cell. (3rd August 2018) - Pan, Zhefei; Huang, Bin; An, Liang
Summary: In this work, a hybrid fuel cell is developed and tested, which is composed of an alkaline anode, an acid cathode, and a cation exchange membrane. In this fuel cell, ethylene glycol and hydrogen peroxide serve as fuel and oxidant, respectively. Theoretically, this fuel cell exhibits a theoretical voltage reaching 2.47 V, whereas it is experimentally demonstrated that the hybrid fuel cell delivers an open‐circuit voltage of 1.41 V at 60°C. More impressively, this fuel cell yields a peak power density of 80.9 mW cm −2 (115.3 mW cm −2 at 80°C). Comparing to an open‐circuit voltage of 0.86 V and a peak power density of 67 mW cm −2 previously achieved by a direct ethylene glycol fuel cell operating with oxygen, this hybrid direct ethylene glycol fuel cell boosts the open‐circuit voltage by 62.1% and the peak power density by 20.8%. This significant improvement is mainly attributed not only to the high‐voltage output of this hybrid system design but also to the faster kinetics rendered by the reduction reaction of hydrogen peroxide. Abstract : This article develops a hybrid direct ethylene glycol fuel cell consisting of an alkaline anode, a cation exchange membrane, and an acid cathode, resulting in a peak power density of 115.3 mW cm −2 at 80°C. A hybrid direct ethylene glycol fuel cell is proposed. This hybrid DEGFC exhibits a theoretical voltage as high as 2.47 V. It exhibits a peak power density of 115.3 mW cm −2 at 80°C. This fuel cell shows a 20.8% increase in peak power density than the same fuel cell using oxygen. The effects of operation conditions on cell performance are investigated.